Transformational leadership contributions and job satisfaction in the development of innovative behavior of employees - Dewi Tri Wijayati (Journal of Economics, Business, and Accountancy Ventura, 2014)
PLN (State-owned Electricity Company) in North Surabaya area are demanded to always improve their services to the public. The service improvement needs to be done for the electrical energy needs of the community that is always increasing. The leaders are supposedly able to apply transformational leadership in fostering innovative behavior of employees. In addition, the employees must also be satisfied with their jobs so as to encourage innovative behavior. This study aims to determine the direct effect transformational leadership and job satisfaction on the employees’ innovative behavior, especially in North Surabaya Area Office PLN. This quantitative study took 57 employees of PLN office in North Surabaya area using probability sampling method and simple random sampling technique. Data analysis was done by using descriptive analysis with the statistical average of the category Three-box Method and inferential analysis using Partial Least Square (PLS). It shows namely: (a) transformational leadership affects the innovative behavior of employees (b) job satisfaction affects the innovative behavior of employees (c) leadership transformational affects job satisfaction (d) transformational leadership and job satisfaction influences the innovative behavior of employees and (e) leadership transformational effect on employee satisfaction.